Animation Programs Of Islamic Television: A Study Of Al-Hijrah Television Channel - Osama Kanaker; Zulkiple Abd Ghani (Universiti Sains Islam Malaysia, 2024)
This paper focuses on animation programs presented on al-Hijrah television channel. Al-Hijrah is the Islamic television channel in Malaysia. This study is a programs analysis of the target audience and the topic of the animation programs to find out whether al-Hijrah uses animation as a tool for distributing the Islamic message in an attractive format to audience. The main finding is that al-Hijrah allocates animation not only for children but to the general audience too. Animation of al-Hijrah are not only religious programs, they are a combination of religious and life matters.